2018
DOI: 10.1111/jgs.15460
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Morbidity at Extreme Old Age in Germany: An Observational Study Using Health Claims Data

Abstract: We assessed the prevalence of morbidity in long-lived individuals according to age and age at death and explored the association between dementia and other diseases and surviving to age 90 and 100. Using health claims data from the largest German health insurer from 2004 to 2013, we followed birth cohorts from 1908 to 1913 from age 95 until death or survival to age 100 (n=2,865) and compared them with birth cohorts from 1918 to 1923 and their survival from age 85 to age 90 (n=17,013). We observed their exact d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
2
10
0
1
Order By: Relevance
“…Other authors have documented similar findings, suggesting that conditions with high mortality risk are more prevalent in younger age groups [ 34 , 50 ]. A study showed that, at the same age, those living longer had a lower prevalence of most chronic diseases than those who died at an earlier age; the authors reported remarkable differences regarding dementia and chronic heart disease [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have documented similar findings, suggesting that conditions with high mortality risk are more prevalent in younger age groups [ 34 , 50 ]. A study showed that, at the same age, those living longer had a lower prevalence of most chronic diseases than those who died at an earlier age; the authors reported remarkable differences regarding dementia and chronic heart disease [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We included 23 major age‐related diseases 20 and risk factors for dementia according to the factors reported by the Lancet Commission 21 (see Table S1 for the respective ICD codes). In addition, we included all medical prescriptions coded by the German version of the ATC classification system on the 3rd level (pharmacological subgroup), and all surgeries based on three‐digit classes from Chapter 5 of the OPS.…”
Section: Methodsmentioning
confidence: 99%
“…Through a PubMed literature review focused on dementia excess mortality and relative risk spanning 1980 to 2018, we identified 4470 total hits, of which 34 studies were marked for extraction (additional details in supporting information) 23–56 . The data sources included clinical or community‐based cohorts and excluded studies conducted solely in nursing homes.…”
Section: Methodsmentioning
confidence: 99%